Whole-genome sequencing identified novel mutations in a Chinese family with lynch syndrome - He, Wan; Dong, Shaowei; Shen, Jing; Wu, Jiutong; Zhao, Pan; Li, Dongbing; Wang, Dongliang; Tang, Na; Zou, Chang (Frontiers in Oncology, 2023)
ackground: Lynch syndrome (LS) is caused by a germline mutation in one of the mismatch repair genes (MLH1, MSH2, MSH6, and PMS2) or in the EPCAM gene. The definition of Lynch syndrome is based on clinical, pathological, and genetic findings. Therefore, the identification of susceptibility genes is essential for accurate risk assessment and tailored screening programs in LS monitoring. Patients and methods. In this study, LS was diagnosed clinically in a Chinese family using Amsterdam II criteria. To further explore the molecular characteristics of this LS family, we performed whole genome sequencing (WGS) to 16 members in this family and summarized the unique mutational profiles within this family. We also used Sanger sequencing technology and immunohistochemistry (IHC) to verify some of the mutations identified in the WGS analysis. Results. We showed that mutations in mismatch repair (MMR) related genes, as well as pathways including DNA replication, base excision repair, nucleotide excision repair, and homologous recombination were enhanced in this family. Two specific variants, MSH2 (p.S860X) and FSHR (p.I265V) were identified in all five members with LS phenotypes in this family. The MSH2 (p.S860X) variant is the first reported variant in a Chinese LS family. This mutation would result in a truncated protein. Theoretically, these patients might benefit from PD-1 (Programmed death 1) immune checkpoint blockade therapy. The patients who received nivolumab in combination with docetaxel treatments are currently in good health. Conclusion. Our findings extend the mutation spectrum of genes associated with LS in MLH2 and FSHR, which is essential for future screening and genetic diagnosis of LS. Keywords: Lynch syndrome, whole genome sequencing, MMR pathway, MSH2, FSHR